One piece. Collection no. 06 [videorecording (DVD)] - Oda, Eiichirō, 1975- (FUNimation Productions, 2012)
Fresh off their adventure in Alabasta, The Straw Hats prepare to sail straight into the sky! After a death-defying adventure in the dire and dangerous Rainbow Mist, Luffy and his crew dock at Mock Town in search of directions, but instead they're brutally bullied by pirates who've forgotten how to dream. Fortunately for the sake of adventure, Nico Robin catches wind of a legendary liar whose monkey minions can equip any ship for a deadly ascent on the Knockup Stream.